Buckling Behaviour of Carbon-Epoxy Adhesively-Bonded Scarf Repairs - Raul Duarte Salgueiral Gomes Campilho (2009)
The presentworkisdedicatedtotheexperimentalandnumericalstudyofthebucklingbehaviourunderpure compression ofcarbonepoxyadhesively-bondedscarfrepairs,withscarfanglesvaryingfrom2to45. The experimentalresultswereusedtovalidateanumericalmethodologyusingtheFiniteElementMethod and amixed-modecohesivedamagemodelimplementedintheABAQUS® software.Theadhesivelayer wassimulatedusingcohesiveelementswithtrapezoidaltractionseparationlawsinpuremodesIandIIto account fortheductilityoftheadhesiveused.ThecohesivelawsinpuremodesIandIIweredetermined with DoubleCantileverBeamandEnd-NotchedFlexuretests,respectively,usinganinversemethod.Since in theexperimentsinterlaminarandtransverseintralaminarfailuresalsooccurred,cohesivelawstosimulate these failuremodeswerealsoobtainedexperimentallyfollowingasimilarprocedure.Goodcorrelations were foundbetweenthenumericalpredictionsandexperimentalresultsfortheelasticstiffness,maximum load andthecorrespondingdisplacement,plateaudisplacementandfailuremodeoftherepairs.